Pyrolysis: An effective technique for degradation of COVID-19 medical wastes. (July 2021) - Dharmaraj, Selvakumar; Ashokkumar, Veeramuthu; Pandiyan, Rajesh; Halimatul Munawaroh, Heli Siti; Chew, Kit Wayne; Chen, Wei-Hsin; Ngamcharussrivichai, Chawalit
Abstract: COVID-19 has led to the enormous rise of medical wastes throughout the world, and these have mainly been generated from hospitals, clinics, and other healthcare establishments. This creates an additional challenge in medical waste management, particularly in developing countries. Improper managing of medical waste may have serious public health issues and a significant impact on the environment. There are currently three disinfection technologies, namely incineration, chemical and physical processes, that are available to treat COVID-19 medical waste (CMW). This study focuses on thermochemical process, particularly pyrolysis process to treat the medical waste. Pyrolysis is a process that utilizes the thermal instability of organic components in medical waste to convert them into valuable products. Besides, the technique is environmentally friendly, more efficient and cost-effective, requires less landfill capacity, and causes lower pollution. The current pandemic situation generates a large amount of plastic medical wastes, which mainly consists of polyethylene, polypropylene, polystyrene, polyethylene terephthalate, and nylon. These plastic wastes can be converted into valuable energy products like oil, gas and char through pyrolysis process. This review provides detailed information about CMW handling, treatment, valuable product generation, and proper discharge into the open environment. Graphical abstract: Image 1 Highlights: COVID-19 has led to the increase of medical and plastic wastes, which threats the environment. The disinfection technologies to treat the COVID medical waste. Pyrolysis an ecofriendly and effective technology for decomposing medical and plastic waste. Conversion of COVID19 medical and plastic waste to Energy.